INOVASI PEMBELAJARAN IPA PADA MASA PANDEMI COVID 19 - Lilis Suriaty Ismail Bereki (Jurnal Pendidikan Sang Surya, 2022)
Abstract:  The purpose of this study is to describe (1) natural science learning innovations during the Covid 19 pandemic and (2) the impact of innovations on natural science learning. The data was collected through documentation and conducting reviews related to natural science learning during the Covid 19 pandemic which was published in national journals. The data that has been collected is then analyzed through four stages, namely data collection, data reduction, data presentation and drawing conclusions. The findings show that (1) natural science learning innovations carried out during the pandemic include learning tools that are oriented towards student creativity, Digital Student Worksheets (LKPD), the use of video-based learning media, android-based learning media, the application of learning desai in the form of Problem Based Learning (PBL), Project Based Learning (PjBL) and inquiri, the use of online platforms such as google classroom, learning houses, edmodo, whatsapp and further innovation in the form of the use of learning media that contain game content (games) and also the use of ice breaking in learning natural sciences; (2) natural science learning innovation has a positive impact on several aspects, including improving natural science learning outcomes, increasing students  science literacy, increasing students critical thinking ability, increasing students' natural science learning motivation, growing student creativity in participating in natural science learning and improving process skills in learning natural sciences.